2006
DOI: 10.1021/bi060107k
|View full text |Cite
|
Sign up to set email alerts
|

Deducing the Transmembrane Domain Organization of Presenilin-1 in γ-Secretase by Cysteine Disulfide Cross-Linking

Abstract: Abstractγ-Secretase is a founding member of membrane-embedded aspartyl proteases that cleave substrates within transmembrane domains, and this enzyme is an important target for the development of therapeutics for Alzheimer's disease. The structure of γ-secretase and its precise catalytic mechanism still remain largely unknown. γ-Secretase is a complex of four integral membrane proteins, with presenilin (PS) as the catalytic component. To gain structural and functional information about the 9-transmembrane doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…Thus, we speculate that the C-terminal region of TMD1 is an essential domain for maintaining the integrity of PS1 structure via hydrophobic interactions with other TMDs. The observation that C92 in TMD1 was cross-linked with C410 or C419 in TMD8, the latter being totally embedded within the lipid bilayer (Sato et al, 2008), by oxidation-mediated crosslinking (Kornilova et al, 2006), supports this view.…”
Section: Discussionmentioning
confidence: 63%
“…Thus, we speculate that the C-terminal region of TMD1 is an essential domain for maintaining the integrity of PS1 structure via hydrophobic interactions with other TMDs. The observation that C92 in TMD1 was cross-linked with C410 or C419 in TMD8, the latter being totally embedded within the lipid bilayer (Sato et al, 2008), by oxidation-mediated crosslinking (Kornilova et al, 2006), supports this view.…”
Section: Discussionmentioning
confidence: 63%
“…Thus, these mutations seem to be well tolerated and do not affect significantly the structure of PS1, as assessed in our cell biological experiments. Recently, Kornilova et al (42) have suggested that cysteines Cys-92, -410, and -419 may contribute to the active site of PS1. However, they did not check to what extent their replacement with serine (or alanine) interferes with this function.…”
Section: Discussionmentioning
confidence: 99%
“…Tyr389 may also contribute to the catalytic site . The conformation of the active site also depends on more remote sequences within PS1, such as the C-terminal PAL motif and Cys residues in TMD1 and TMD8 (Kornilova et al, 2006). Binding of an active-site-directed inhibitor prevents the disulphide cross-linking between TMD1 and TMD8, implicating their close proximity to or allosteric interaction with the catalytic site.…”
Section: Introductionmentioning
confidence: 99%
“…What the low-resolution 3D-EM does not reveal is how and where NCT, APH1 and PEN2 associate in the complex relative to PS or the contribution of TMDs bordering the translucent inner space. The lateral thin-density regions may for instance represent interfaces between different components, PS heterodimers [TMD1-TMD8 (Kornilova et al, 2006)] [TMD6-TMD7 (Sato et al, 2006;Tolia et al, 2006)] or even two PS molecules. Indeed, some studies indicate that the catalytic core consists of a PS dimer, one PS providing the substrate-binding site and the other the catalytic cleavage site (Cervantes et al, 2004;Schroeter et al, 2003).…”
Section: Introductionmentioning
confidence: 99%